Siting Suitability Analysis of Petrol Filling Station using GIS and Analytical Hierarchy Process: A Case Study of Surabaya Metropolitan - Aulia, Belinda Ulfa (2011)
ABSTRACT Petrol filling stations (PFS) are among those that have high potential of fire hazard due to the dangerous material that they store. Hence their siting should be carried out properly. Their improper siting could lead to disastrous consequences during fire and could cause pollution to surrounding soil and underground water should leakage occur to their underground storage tanks. Therefore, the bjectives of this study is to assist the proper siting of new stations and assess the locationsuitability location of existing petrol filling stations. A suitable petrol filling station siting must incorporate environmental safety criteria and attributes that will enable them to be located in safe locations so that no unacceptable risk to people or the environment would exist. In the Surabaya metropolitan area, the growth of motor vehicles is around 12% per year and the total number of cars and motorcycles is up to 1.6 million. Such growth creates the need to establish new petrol filling stations to add to the 90 stations already in existence. This study performs the integration between Geographic Information System (GIS) and Analytic Hierarchy Process (AHP) for siting suitability assessment. The GIS with spatial analysis provides an opportunity to identify suitable site by computing various criteria based on environmental consideration. On the other hand, AHP is applied to quantify the priority ranking of each criteria based on stakeholders preference. This integration is called spatial multicriteria decision support system that will help to find suitable sites based on priority preference. At the end of this study, PFS sites in Surabaya have been classified as highly suitable zone, moderately suitable area, and less suitable zone. As a result, the integration of GIS and AHP has uncovered fact that 85.5% of the total numbers of existing PFS in Surabaya are not located in highly suitable zone. As conclusion, this study shows that GIS and AHP are essential tools to assist correct siting of PFS.